Prediction of alcohol use disorder using personality disorder traits: a twin study. (23rd August 2017) - Rosenström, Tom; Torvik, Fartein Ask; Ystrom, Eivind; Czajkowski, Nikolai Olavi; Gillespie, Nathan A.; Aggen, Steven H.; Krueger, Robert F.; Kendler, Kenneth S.; Reichborn‐Kjennerud, Ted
Abstract: Background and Aims: The DSM‐IV personality disorders (PDs) are comorbid with alcohol use disorder (AUD) and with each other. It remains unclear which PD criteria are most likely to drive onset and recurrence of AUD and which are merely confounded with those criteria. We determine which individual PD criteria predict AUD and the degree of underlying genetic and/or environmental aetiology. Design: A prospective observational twin study. Setting: Norway 1999–2011. Participants: A total of 2528 and 2275 Norwegian adult twins in waves 1 and 2 variable‐selection analyses, and 2785 in biometric analyses. Measurements: DSM‐IV PDs and their 80 criteria were assessed using a structured personal interview, and AUD using the World Health Organization's Composite International Diagnostic Interview. Findings: In a variable‐selection analysis, two PD criteria were associated with AUD even after taking all the other criteria into account: criterion 8 of antisocial PD (childhood conduct disorder) and criterion 4 of borderline PD (self‐damaging impulsive behaviours). Adjusting for each other, their respective odds ratios were 3.4 [confidence interval (CI) = 2.1–5.4] and 5.0 (CI = 3.3–7.7). Endorsement strength of the criteria was associated with AUD in a dose–response manner and they explained 5.5% of variation in AUD risk—more than the full diagnoses of antisocial and borderline PDs together (0.5%). The association between borderline criterion 4 and AUD 10 years later derived mainly from their overlapping genetic factors, whereas the association between antisocial criterion 8 and AUD 10 years later was due to both genetic and non‐genetic factors. Conclusions: Conduct disorder and self‐harming impulsivity are the foremost risk traits for alcohol use disorder among the 80 personality disorder criteria of DSM‐IV, predicting alcohol use disorder more effectively than personality disorder diagnoses. The twin‐study analysis suggested that conduct disorder represents a joint genetic and developmental risk for alcohol use disorder and that impulsivity is a genetic risk.